2003
DOI: 10.1002/app.13166
|View full text |Cite
|
Sign up to set email alerts
|

Graft‐modified HCPE with methyl methacrylate by the mechanochemistry reaction. II. Physical‐mechanical properties and processability

Abstract: ABSTRACT:In this article, the physical-mechanical properties and processability of graft-modified highly chlorinated polyethylene (HCPE; chlorine contents: Ն 60%) with methyl methacrylate (MMA) by mechanochemistry reaction were studied. The results showed that the HCPE-g-MMA system is superior to unmodified HCPE in physical-mechanical properties, particularly in processability. In addition, the HCPE-g-MMA system, with about 62% chlorine content, was the same as PVC in its physical-mechanical properties. The HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Besides the seemingly purely destructive process of mastication, recent efforts demonstrate the feasibility of using mechanoradicals for controlled polymerization and copolymerization by grinding and milling. Schmidt-Naake and co-workers demonstrated the controlled synthesis of block and graft copolymers in a vibratory mill. , Graft-modified highly chlorinated polyethylene with methylmethacrylate was prepared mechanochemically by Zhao et al and showed promising material properties . Cross-linking was observed upon mechanical milling of polyisoprene at cryogenic conditions by Spontak and co-workers .…”
Section: 14 Technological Relevance Of Polymer Mechanochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the seemingly purely destructive process of mastication, recent efforts demonstrate the feasibility of using mechanoradicals for controlled polymerization and copolymerization by grinding and milling. Schmidt-Naake and co-workers demonstrated the controlled synthesis of block and graft copolymers in a vibratory mill. , Graft-modified highly chlorinated polyethylene with methylmethacrylate was prepared mechanochemically by Zhao et al and showed promising material properties . Cross-linking was observed upon mechanical milling of polyisoprene at cryogenic conditions by Spontak and co-workers .…”
Section: 14 Technological Relevance Of Polymer Mechanochemistrymentioning
confidence: 99%
“…132,135 Graft-modified highly chlorinated polyethylene with methylmethacrylate was prepared mechanochemically by Zhao et al and showed promising material properties. 142 Crosslinking was observed upon mechanical milling of polyisoprene at cryogenic conditions by Spontak and co-workers. 130 In the recycling of polymeric waste by shear pulverization, formation of mechanoradicals is probably a desired effect, which aids the in situ compatibilization of commingled plastic waste by formation of block and graft copolymers.…”
Section: Technological Relevance Of Polymer Mechanochemistrymentioning
confidence: 99%
“…Grafting is one of the commonly used modification methods to modify CPE, being used to introduce polar groups to overcome its shortage in properties and endow new performances by the polarity and reactivity of these introduced polar groups. [4,5,[7][8][9][10][11][12] The grafting methods of CPE mainly include solution grafting, [10] suspension grafting in water, [11] and mechanochemisry grafting. [7,12] To our knowledge, solid-state grafting is often used to modify polyolefins but is less used to graft CPE.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5,[7][8][9][10][11][12] The grafting methods of CPE mainly include solution grafting, [10] suspension grafting in water, [11] and mechanochemisry grafting. [7,12] To our knowledge, solid-state grafting is often used to modify polyolefins but is less used to graft CPE. The grafting process by solid-state reaction can be carried out at relatively low temperature and normal pressure, without solvent, which is environmental friendly and has low power consumption.…”
Section: Introductionmentioning
confidence: 99%